Current and future carbon stocks in coastal wetlands within the Great Barrier Reef catchments. (4th May 2021) - Duarte de Paula Costa, Micheli; Lovelock, Catherine E.; Waltham, Nathan J.; Young, Mary; Adame, Maria F.; Bryant, Catherine V.; Butler, Don; Green, David; Rasheed, Michael A.; Salinas, Cristian; Serrano, Oscar; York, Paul H.; et al.
Abstract: Australia's Great Barrier Reef (GBR) catchments include some of the world's most intact coastal wetlands comprising diverse mangrove, seagrass and tidal marsh ecosystems. Although these ecosystems are highly efficient at storing carbon in marine sediments, their soil organic carbon (SOC) stocks and the potential changes resulting from climate impacts, including sea level rise are not well understood. For the first time, we estimated SOC stocks and their drivers within the range of coastal wetlands of GBR catchments using boosted regression trees (i.e. a machine learning approach and ensemble method for modelling the relationship between response and explanatory variables) and identified the potential changes in future stocks due to sea level rise. We found levels of SOC stocks of mangrove and seagrass meadows have different drivers, with climatic variables such as temperature, rainfall and solar radiation, showing significant contributions in accounting for variation in SOC stocks in mangroves. In contrast, soil type accounted for most of the variability in seagrass meadows. Total SOC stock in the GBR catchments, including mangroves, seagrass meadows and tidal marshes, is approximately 137 Tg C, which represents 9%–13% of Australia's total SOC stock while encompassing only 4%–6% of the total extent of Australian coastal wetlands. In a global context, this could represent 0.5%–1.4% of global SOC stock. Our study suggests that landward migration due to projected sea level rise has the potential to enhance carbon accumulation with total carbon gains between 0.16 and 0.46 Tg C and provides an opportunity for future restoration to enhance blue carbon. Abstract : Australia's Great Barrier Reef (GBR) catchments include some of the world's most intact coastal wetlands comprising mangrove, seagrass and tidal marsh ecosystems. However, their soil carbon stocks (SOC) and future changes under predicted climate change scenarios are not well understood. We estimated total SOC within the GBR catchments in approximately 137 Tg C, which represents 9%–13% of Australia's total SOC stock while encompassing only 4%–6% of the total extent of Australian coastal wetlands. Landward migration due to projected sea level rise by 2100 has the potential to enhance SOC stocks with total carbon gains between 0.16 and 0.46 Tg C and provides an opportunity for future restoration projects to enhance blue carbon. ​